2022
DOI: 10.3389/fsurg.2022.868663
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Successful Repair of Primary Aortoesophageal Fistula With an Endovascular Stent Graft and an Esophageal Stent

Abstract: Aortoesophageal fistula (AEF), secondary to thoracic pseudoaneurysm as a result of upper gastrointestinal bleeding, is a rare condition and will be undoubtedly lethal without prompt surgical intervention. The estimated annual incidence of primary AEFs and secondary AEFs is about 0.0015% and 0.6%–2%, respectively. The challenges of the therapy posed by AEF are control of the hemorrhage, arterial reconstruction in an infection field, control of sepsis, and re-establishment of the alimentary tract. We present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…AEF are classified as primary (0.0015%) and secondary (0.6–2%) [ 2 , 3 ]. Primary AEF is mostly caused by thoracic aortic aneurysms (51%), while other causes include penetrating aortic ulcer, esophageal cancer, ingestion of foreign bodies, Barrett’s ulcer, trauma, or prolonged nasogastric tube intubation [ 4 , 5 ].…”
Section: Review and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…AEF are classified as primary (0.0015%) and secondary (0.6–2%) [ 2 , 3 ]. Primary AEF is mostly caused by thoracic aortic aneurysms (51%), while other causes include penetrating aortic ulcer, esophageal cancer, ingestion of foreign bodies, Barrett’s ulcer, trauma, or prolonged nasogastric tube intubation [ 4 , 5 ].…”
Section: Review and Discussionmentioning
confidence: 99%
“…Aortoesophageal syndrome in AEF was first described by Chiari in 1914 as a sequence of dysphagia or mid-thoracic pain, sentinel minor bleeding expressed as minor hemoptysis or hematemesis, followed by a symptom-free period before a major bleeding event with exsanguination. (1,3,10) However, in a review of the literature consisting of more than 500 cases, only 45% of the patients presented with classical Chiari's triad, while herald bleeding was found in 65% of the cases, mid-thoracic pain in 59%, and dysphagia in 45% of the cases [5]. Another study identified hematemesis as the most common symptom of AEF [1].…”
Section: Clinical Presentationmentioning
confidence: 99%
See 3 more Smart Citations